Studi Instrumen Kebijakan dalam Upaya Percepatan Penurunan Stunting Kota Kediri - Fathoni, M Agus (Penerbit Goodwood, 2025)
Purpose: This study aimed to identify and describe the policy instruments used by the Kediri City Government to accelerate stunting reduction. Methodology/approach: A qualitative approach was employed in Kediri City through in-depth interviews with officials from the health department and a literature review. Data were collected using interview guides and relevant policy documents to understand the strategies and barriers to reducing stunting. Results/findings: Five main policy instruments were identified: family and community engagement, voluntary organizations, information and exhortation campaigns, subsidies, and regulatory policies. However, several obstacles hindered their effectiveness in the past. These include poor parenting practices, particularly in infant feeding (such as lack of exclusive breastfeeding and improper complementary feeding), parents’ refusal to consult pediatricians, and failure to follow prescribed special dietary interventions (PKMK) for toddlers with stunted growth. Conclutions: Although the Kediri City Government has implemented various appropriate policies, success is constrained by limited parental knowledge and awareness. To improve outcomes, greater emphasis should be placed on targeted education and personalized outreach, particularly for families with children with stunted growth. Strengthening the role of local institutions and leveraging existing community networks can enhance the dissemination and adoption of appropriate stunting management practices. Limitations: This study focused on only five types of policy instruments observed in the field. Future studies should explore additional instruments to achieve a more comprehensive understanding. Contribution: This study provides practical insights into local government policy tools for tackling stunting, offering a reference for other regions aiming to implement or enhance similar initiatives in the future.